Shaping South Asia's future role of regional cooperation - Bhargava, K. K. (Kant Kishore); Bongartz, Heinz; Sobhan, Farooq (Vikas Pub. House, 1995)
Papers presented at a Conference on "Shaping South Asia's Future: Role of Regional Cooperation" in Kathmandu, 1994, organized by Friedrich-Ebert-Stiftung.